Röm. Provinz Baetica, Spanien. Arbeiten zum Corpus Inscriptionum Latinarum II - Rothenhöfer, Peter (e-Forschungsberichte des DAI, 2023)
The current work focuses on the ancient Latin inscriptions from the province of Baetica. Actually, the manuscript of the volume Hispalensis North, i.e. the northern part of the judicial district of Hispalis (Seville), is prepared for printing. It includes about 900 inscriptions, about four and a half times more entries for this area than in the first volumes edited by Emil Hübner. These 900 inscriptions spread over 27 ancient administrative units, which usually are cities with their territories, with the exception of an imperial mining district which existed around the rich deposits of the Iberian Pyrite Belt in the north of the province of Huelva. The increase in inscriptions makes it possible to draw a noticeably sharper picture of the historical geography of the Western part of the Roman province of Baetica. This mainly concerns the localization of cities and the territorial structure associated with it, but also our knowledge of the judicial status of cities. Moreover, in 2013 work intensified on inscriptions from the south of the judicial district of Hispalis. Furthermore, first complexes from the western part of the conventus Gaditanus are in preparation.